The Role of Islamic Organizational Culture on the Performance of Islamic Bank Employees - Zulfadli Hamzah; Muhammad Arif; Mufti Hasan Alfani; Putri Nuraini; Hamsal Hamsal; Mohd Izzat bin Mohd Abd Shukur (Penerbit Goodwood, 2026)
Purpose: The aim of this research was to determine how the influence of Islamic organizational culture on the performance of Islamic bank employees in Riau Province Methodology: This research employs a simple regression analysis with the population of all Islamic bank employees in Riau Province, while the research sample was 353 using the Slovin Formula. Results: The results of this study concluded that Islamic Organizational Culture has a significant effect on the performance of Islamic bank employees in Riau Province. Conclusions: This study confirms that Islamic organizational culture, grounded in the fundamental principles of tawhid, khilafah, and ‘adl, plays a substantial role in shaping employee performance. These values not only function as ethical guidelines but also foster responsibility, accountability, and commitment to work, which ultimately enhances overall performance outcomes in Islamic banking institutions. Limitations: This research has limitations in using more comprehensive Islamic variables and methods to determine the factors affecting Islamic bank employee performance. Contributions: This study empirically supports Islamic organizational culture as a significant determinant of employee performance in Sharia-based banking institutions and provides quantitative evidence from Islamic banks in Riau Province.